2011
DOI: 10.5688/ajpe758157
|View full text |Cite
|
Sign up to set email alerts
|

A Course Assessment Process for Curricular Quality Improvement

Abstract: Objective. To describe a systematic assessment process that provides continuous improvement in the curriculum, supports faculty development, and enhances student learning outcomes. Design. Teams of faculty members, students, and course instructors conducted course assessments, which consisted of monitoring the delivered instruction for agreement with planned content and course integration within the curriculum, and providing ongoing feedback for improving course content, course management, faculty teaching, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Penn State's IMPROVE model, which is an expansion of Shewhart (1939)/Deming (1986) 'plan-do-check [study]-act' model, demonstrates how to facilitate problem solving, decision making, and process improvement in higher education (Kelly, 2010). Peterson et al (2011) have described a systematic assessment process that provides CI in the curriculum, supports faculty development, and enhances student learning outcomes and concluded that the curriculum assessment plan provides a structured method of monitoring and delivering continuous quality improvement. Haug and Keleman (1996) have discussed about CI concept and related tools in the context of introducing total quality management (TQM) into the process of teaching management.…”
Section: Attainment Of Student Learning Objectives Through 'Ci'mentioning
confidence: 99%
“…Penn State's IMPROVE model, which is an expansion of Shewhart (1939)/Deming (1986) 'plan-do-check [study]-act' model, demonstrates how to facilitate problem solving, decision making, and process improvement in higher education (Kelly, 2010). Peterson et al (2011) have described a systematic assessment process that provides CI in the curriculum, supports faculty development, and enhances student learning outcomes and concluded that the curriculum assessment plan provides a structured method of monitoring and delivering continuous quality improvement. Haug and Keleman (1996) have discussed about CI concept and related tools in the context of introducing total quality management (TQM) into the process of teaching management.…”
Section: Attainment Of Student Learning Objectives Through 'Ci'mentioning
confidence: 99%
“…6 Our program is similar to this example and other published course review procedures in that it uses a standardized data collection platform. 7 However, while some information (such as the instructor's responses to the questionnaire) can be extracted from the online survey for review, copies of syllabi and course materials are not retained as part of the online data collection process and the online system is not a searchable, robust database. 6 One other difference between our program and others is that our program's initial review is done by one committee member, rather than a review team.…”
Section: Discussionmentioning
confidence: 99%
“…1 Examples of published curricular quality improvement processes in the pharmacy and medical literature are growing, with several papers that describe processes to examine and make improvements to didactic and experiential courses. [2][3][4][5][6][7] Established, ongoing curricular review processes are imperative to ensure course materials, teaching strategies, and assessments are appropriate to adequately prepare practice-ready pharmacists. While published examples demonstrate the importance of curricular mapping to outcomes using course syllabi, formalized systematic review remains a challenge in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…While all these factors should be evaluated, the literature regarding pharmacy faculty evaluation has focused largely on classroom teaching, [2][3][4][5][6][7][8][9][10][11][12] with the most common evaluation strategies being peer assessment of classroom teaching [5][6][7][8] and student evaluations (print and Web-based). [9][10][11][12][13] There is a paucity of published data regarding the assessment/evaluation of faculty members in experiential or clinical teaching settings.…”
Section: Introductionmentioning
confidence: 99%